ROLE OF HETEROZYGOUS TUMOR SUPPRESSORS IN THE LIFE LONGEVITY OF DROSOPHILA MELANOGASTER - S. A. Kopyl; L. V. Omelyanchuk; M. V. Shaposhnikov; A. A. Moskalev (Вавиловский журнал генетики и селекции)
Role of tumor-suppressor genes in the life longevity has not been studied in detail. The purpose of the current work is to study the influence of heterozygous tumor suppressors on the life span of drosophila. We show that heterozygotes for l(3)hem, hyd, gd, ex or ft, both females and males, have a shorter life. The analysis of Gompertz curve parameters indicates that the l(3)hem, hyd or gd mutations increase age-related parameter (α) in males, while gd mutation increases the death background parameter (R) and the ex agerelated parameter in females. The effects of the mutations on the life span are probably associated with hedgehog (hyd), Notch (gd) и Hippo (ex и ft) signal transduction pathways.